Improving diets with wild and cultivated biodiversity from across the landscape - Powell, B.; Thilsted, Shakuntala H.; Ickowitz, A.; Termote, Céline; Sunderland, Terry C.H.; Herforth, A. (Springer, 2015)
This paper examines the literature on how biodiversity contributes to improved and diversified diets in developing countries. We assess the current state of evidence on how wild and cultivated biodiversity in all forms is related to healthy diets and nutrition, and examine how economic factors, knowledge and social norms interact with availability of biodiversity to influence both production and consumption choices. The paper identifies areas where evidence is lacking and ways to build synergies between nutrition-sensitive approaches and efforts to ensure sustainability of food systems and the natural environment.